Empowerment of PKK Wanagiri Group Through the Application of Natural Preservative Aloe-coating on Strawberries - Suriati, Luh; Selamet, K (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Postharvest handling of strawberries is an effort to prevent damage, maintain quality and extend shelf life. The application of the edible coating is a step that can be taken in the postharvest handling of strawberries. The number of harmful preservatives on the market is a cause for concern. Aloe vera gel is a natural ingredient that can be used as an edible coating for strawberries. Empowerment of community groups in the application of natural preservative Aloe-coating on strawberries can overcome the problems that exist in the community. One of the groups in the villages that has this problem is the Empowering Family Welfare Group PKK Wanagiri, which is located in Sukasada District, Buleleng Regency, Bali Province, Indonesia. Partners do not know post-harvest handling, entrepreneurship, and marketing. The solutions to solve the problems are: providing knowledge about post-harvest handling, packaging, entrepreneurship, and marketing. Appropriate technology on how to make Aloe-coating and methods of its application to strawberries are provided and quality can be maintained. The method used is active community participation and exploratory. The result is community service activities have been running smoothly. The PKK Wanagiri, get the added value and their standard of living has increased. Post-harvest handling of strawberries can be applied. Knowledge of Aloe-coating produce, method of application, packaging, hygiene sanitation, entrepreneurship, and appropriate product marketing was understood and applied. This activity is carried out continuously and the group can independently make aloe vera coating, and apply it to strawberries, thereby increasing income.